Edukasi Hemat Energi dan Penerapan Teknologi IoT di SMP IT Al-Kholis Lampung Selatan - Purwono Prasetyawan; Amelia Oktavia; Uri Arta Ramadhani; Lanang Almasyuri; Miftahul Donny Sanjaya (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
SMP IT Al-Kholis uses PLN electricity to support teaching and learning activities. Some of the electrical loads that are widely used at the school are lamps and fans in the classrooms, halls, offices, and dormitories. Sometimes, lamps and fans remain connected to the electrical plug when not being used. Several classrooms and corridors are still using fluorescent lamps which are not efficient in terms of energy utilization.Therefore, in this case, energy efficiency along with conservation methods are highly necessary to be implemented. Energy conservation put more focused on improving energy-saving behavior while energy efficiency underlines the selection of efficient instruments. To improve energy-saving behavior, it is important to raise awareness of saving electricity urgency along with some examples of actions on it, by training method. Meanwhile, as for raising awareness of energy efficiency, the demonstration was carried out by providing energy saving lamps integrated with Internet of Things technology. The results of the implementation of this community service activity, include: 1) There is an increase in the number of students who understands the implementation of energy-saving education and IoT technology, as much as 32.66%; 2) Partners gave appreciation and expressed their gratitude for replacing LED lights with PIR motion sensor technology, LDR light sensors, and with solar cells and; 3) the functionality of the IoT-based fan and light monitoring and control system can run well.